Remuneration committee governance and firm performance in UK financial firms - Peter Agyemang-Mintah (LLC “CPC “Business Perspectives”, 2022)
This paper investigates the association between the Remuneration Committee (RC) on firm performance. The research uses a data span of 63 financial institutions for a period of 12 years. Ordinary Least Square (OLS) and Random Effects (RE) regression estimations are used.
The ascertained empirical results indicate that the establishment of remuneration committee by the board is positively correlated to its performance, as measured by its Return on Assets (ROA), and is also statistically significant on the Market Value (MV) of the firm. Subsequent tests conducted show that presence of an RC had a positive  and statistically significant correlation during the pre/post global financial crisis on the ROA of the firm. The MV measure during the pre-crisis indicates a positive and statistically significant impact, but only positive during the post-crisis. The findings are robust across econometric models that control for different types of endogeneity.
The outcome indicates that the establishment of an RC by the Board assisted in achieving a positive impact on the profitability of UK financial institutions.